Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Ulang Konsumen Eat Cake Tulungagung - Riafinola, Roqis; Hastuti, Maria Agatha Sri Widyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this study was to determine the effect of product quality on repurchase interest. Quantitative research type with data analysis using multiple linear regression. The number of samples is 96 respondents. Data collection techniques using questionnaires. Partially, product quality affects repurchase interest, price affects repurchase interest. Simultaneously, product quality and price affect repurchase interest. The results of this study state that product quality has a value t-calculus > t-table namely 2,001 > 1,985, so it can be concluded that there is a positive and significant influence of price on repurchase interest, the price has a value t-calculus > t-table namely 16,703 > 1,985, so it can be concluded that there is a positive and significant influence of price on repurchase interest. Simultaneously it has a value t-calculus (179,244) > t-tabel (3,942) and has a value significance of 0,000 < 0,05. The result of the adjusted R Square value of 79% is the influence of the product quality variabels (X1) and price variabels (X2) and the remaining 21% is influenced by other factors that were not included in this study.